Kekerasan Ekonomi dalam Pacaran sebagai Potret Patologi Sosial atas Nama Cinta - Siti Huzaimah (ACTIVA: Jurnal Ekonomi Syariah, 2019)
This study seeks to explain the violent behavior experienced by victims of economic violence and the reasons for victims of violence while maintaining relations. The method used in this study is a qualitative research method with a phenomenological approach by using observation and interview data collection techniques. Data analysis techniques with the following stages: examine all data, categorize data, connect with the theoretical basis, and draw conclusions. Based on the results of the research that has been done, the researcher concludes that the forms of behavior of economic violence show that the forms of economic violence received by informants include exploitation of property rights, extortion, and utilization of partner resources by their partners in the name of love. By way of borrowing goods belonging to a partner but not returned, asking for money, or buying goods or something but the payer is the woman. There is no doubt that all of these things are pathological actions against their partners in the name of love, and should not occur in dating relationships. Love that is truly holy, beautifully transformed becomes a terrible thing for each partner. Whereas the reasons for the informants to survive in the relationship even if they get violence to the informants are influenced by feelings of love, still hoping their partners can change, there are also because they have no choice even though the informants really want to end the relationship, besides because they have been taken away, everyone knows their relationship.